Severe Hemolytic Crisis in Uncontrolled AIHA Triggered by Dengue - Christian Alberto Rodriguez-Saldaña; Sofía Cavalcanti-Ramírez; Carmen Claudia Quesada-Osoria; Luis Gabriel Farfan-Chavez; Guiovanna María Wong-Terrones; Helena Karin Dominguez-Troncos (Case Reports in Medicine)
We present the case of a woman with a history of autoimmune hemolytic anemia (AIHA), untreated for 1 year, who presented with fever, myalgia, arthralgia, anemia, and thrombocytopenia, along with a positive nonstructural protein antigen 1 (NS1Ag) test. During the course of dengue, the patient developed severe hemolytic anemia, posing a potentially life-threatening scenario due to the rapid decline in hemoglobin levels and the risk of multiorgan failure. Treatment with methylprednisolone was initiated alongside supportive care for dengue, and balancing corticosteroid risks in a viral infection was crucial to stabilize the patient, ultimately leading to a favorable outcome. This case highlights the importance of prompt diagnosis and integrated management of autoimmune diseases and viral coinfections in dengue-endemic areas.